The Effect of Product Quality, Brand Image, and Price on Purchasing Decisions for Branded Used Goods - Lukman, Andi Ainun; Munawir, Munawir; Nurjannah, Nurjannah (Entrepreneurship, Management, and Business Research Journal, 2025)
This study aims to determine the effect of product quality, brand image and price on purchasing decisions for branded used goods. This research is quantitative research with a descriptive approach. The data analysis methods used in this study include validity tests, reliability tests, and normality tests. The research sample consisted of 50 consumers among Andi Djemma University Palopo students. Hypothesis testing was carried out using multiple linear regression analysis. The results showed that product quality, brand image, and price have a positive and significant effect on purchasing decisions for used goods. The implication of this finding is that product quality, brand image and price can increase the purchase of used branded goods in Palopo City, especially among students.